Argon plasma modified nanocomposite polyurethane scaffolds provide an alternative strategy for cartilage tissue engineering - Griffin, Michelle (J Nanobiotechnology, 2019)
BACKGROUND: Children born with a small or absent ear undergo surgical reconstruction to create a suitable replacement using rib cartilage. To overcome the donor site morbidity and long-term pain of harvesting rib cartilage, synthetic materials can be a useful alternative. Medpor, is the currently used synthetic polyethylene material to replace missing facial cartilage but unfortunately it has high levels of surgical complications including infection and extrusion, making it an unsuitable replacement. New materials for facial cartilage reconstruction are required to improve the outcomes of surgical reconstruction. This study has developed a new nanomaterial with argon surface modification for auricular cartilage replacement to overcome the complications with Medpor. RESULTS: Polyurethanes nanocomposites scaffolds (PU) were modified with argon plasma surface modification (Ar) and compared to Medpor in vitro and in vivo. Ar scaffolds allowed for greater protein adsorption than Medpor and PU after 48 h (p < 0.05). Cell viability and DNA assays demonstrated over 14-days greater human dermal fibroblast adhesion and cell growth on Ar than PU and Medpor nanocomposites scaffolds (p < 0.05). Gene expression using RT-qPCR of collagen-I, fibronectin, elastin, and laminin was upregulated on Ar scaffolds compared to Medpor and PU after 14-days (p < 0.05). Medpor, unmodified polyurethane and plasma modified polyurethane scaffolds were subcutaneously implanted in the dorsum of mice for 12 weeks to assess tissue integration and angiogenesis. Subcutaneous implantation of Ar scaffolds in mice dorsum, demonstrated significantly greater tissue integration by H&E and Massons trichrome staining, as well as angiogenesis by CD31 vessel immunohistochemistry staining over 12-weeks (p < 0.05). CONCLUSIONS: Argon modified polyurethane nanocomposite scaffolds support cell attachment and growth, tissue integration and angiogenesis and are a promising alternative for facial cartilage replacement. This study demonstrates polyurethane nanocomposite scaffolds with argon surface modification are a promising biomaterial for cartilage tissue engineering applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-019-0477-z) contains supplementary material, which is available to authorized users.